To what extent do principals of further education colleges display similar leadership traits? - Lambert, Dr. Steve (IJRDO - Journal of Applied Management Science, 2017)
Principals of further education colleges continue to operate in a policy contextdriven by reductions in funding, increasing diversity among the studentpopulation and escalating centralised control. This has meant that principalsare required to rely more on their skills as decision makers and problemsolvers than they have every needed in the past. At the same time, externalinspection has continued to highlight the importance of leadership in enablingstudents to achieve the best possible outcomes, yet as Fink (2010) argues therole of the principal is becoming increasingly unattractive. In order to combata shortage of individuals pursuing principalship positions, organisations aredeveloping their own leadership development programmes; however, little isknown about the behaviours that these programmes should be developing.This paper reports the findings of a series of leadership and psychologicalassessments conducted with principals within the UK. It suggests that despitethe organisational and political challenges facing institutions principalsdemonstrate a largely homogenous set of behaviours which could be used toframe future leadership development programmes.